2013
DOI: 10.1002/stem.1454
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutive activation of RANK disrupts mammary cell fate leading to tumorigenesis

Abstract: Receptor Activator of NF-kappa B (RANK) pathway controls mammary gland development in mice but its role in mammary stem cell fate remains undefined. We show that constitutive RANK signaling expands luminal and basal mammary compartments including mammary stem and luminal progenitor cell pools and interferes with the generation of CD611 and Sca11 luminal cells and Elf5 expression. Impaired mammary cell commitment upon RANK overexpression leads to the accumulation of progenitors including K141K81 bipotent cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 40 publications
11
54
0
1
Order By: Relevance
“…Our results suggest that neoadjuvant RANKL inhibition may be more efficient in reducing recurrence and metastasis than adjuvant treatment, as a significant reduction in the CSC population was observed on tumors treated at passage 1. Along with our previous data demonstrating that overactivation of RANK signaling at midgestation disrupts lactogenesis (12,39), current results suggest that RANK signaling regulates the balance between self-renewal and differentiation not only during mammary gland development but also in breast adenocarcinomas.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results suggest that neoadjuvant RANKL inhibition may be more efficient in reducing recurrence and metastasis than adjuvant treatment, as a significant reduction in the CSC population was observed on tumors treated at passage 1. Along with our previous data demonstrating that overactivation of RANK signaling at midgestation disrupts lactogenesis (12,39), current results suggest that RANK signaling regulates the balance between self-renewal and differentiation not only during mammary gland development but also in breast adenocarcinomas.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous data showed that enhanced RANK activation promotes stemness in human and mouse mammary epithelia, leading to the accumulation of MaSC and progenitors (11,12,39). Importantly, now we demonstrate that inhibition of RANK signaling reduces CSC in invasive mammary tumors decreasing recurrence and metastasis, and induces tumor cell differentiation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Precancerous BRCA1 mut/+ tissue harbors an aberrant population of luminal progenitor cells 1 , and deregulated progesterone signaling has been implicated in BRCA1-associated oncogenesis [2][3][4][5] . Coupled with the findings that tumor necrosis factor superfamily member 11 (TNFSF11; also known as RANKL) is a key paracrine effector of progesterone signaling [6][7][8][9][10] and that RANKL and its receptor TNFRSF11A (also known as RANK) contribute to mammary tumorigenesis [11][12][13] , we investigated a role for this pathway in the pre-neoplastic phase of BRCA1-mutation carriers. We identified two subsets of luminal progenitors (RANK + and RANK − ) in histologically normal tissue of BRCA1-mutation carriers and showed that RANK + cells are highly proliferative, have grossly aberrant DNA repair and bear a molecular signature similar to that of basal-like breast cancer.…”
mentioning
confidence: 99%